2017
DOI: 10.1177/0898264317721348
|View full text |Cite
|
Sign up to set email alerts
|

Pain as a Risk Factor for Loneliness Among Older Adults

Abstract: The results indicate that pain may increase the risk of loneliness in older adults. This suggests that appropriate pain interventions could prevent future loneliness, which in turn could prevent functional decline, disability, and premature mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 26 publications
1
44
2
1
Order By: Relevance
“…15 While the associations between loneliness and later pain parallel previous research, 19 the longitudinal results for pain being related to later loneliness were more robust than those of other population studies. For example, analyses of the Health and Retirement study reported by Emerson et al 12 did not find that baseline pain predicted future loneliness, though the combination of pain both at baseline and follow-up was related to loneliness. Another study of a community sample from Arizona found minimal associations between pain intensity or pain frequency and loneliness measured 6-53 months later.…”
Section: A C C E P T E Dmentioning
confidence: 97%
See 1 more Smart Citation
“…15 While the associations between loneliness and later pain parallel previous research, 19 the longitudinal results for pain being related to later loneliness were more robust than those of other population studies. For example, analyses of the Health and Retirement study reported by Emerson et al 12 did not find that baseline pain predicted future loneliness, though the combination of pain both at baseline and follow-up was related to loneliness. Another study of a community sample from Arizona found minimal associations between pain intensity or pain frequency and loneliness measured 6-53 months later.…”
Section: A C C E P T E Dmentioning
confidence: 97%
“…An investigation of the Health and Retirement Study over a 4 year period indicated that incident loneliness was predicted by pain, but only if pain was present both at baseline and follow-up. 12 Another community study documented cross-sectional associations between pain and loneliness, but found that baseline pain was minimally related to future loneliness. 4 The potentially bidirectional links between pain and loneliness have typically been investigated in separate studies, making it difficult to determine the relative importance of the two temporal sequences.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“… 106 , 107 Chronic pain and long-term illness, on the other hand, increase the risk for loneliness. 108 , 109 Combining virtual social interaction with the relaxation effect of VR nature could thus contribute to both avoiding feeling lonely and to decreasing the risk for illnesses associated with loneliness.…”
Section: Pathways Linking Health With Nature Exposure and The Applicamentioning
confidence: 99%
“…24 Studies have documented there are demographic and physical risk factors associated with loneliness, including lower educational attainment, 25 unemployment, 25 being unmarried, 25 having a physical impairment, 26 and self-reported pain. 23 TBI is associated with all or most of these factors, and the negative consequences of TBI and loneliness share similar sequela. Despite this, the association between TBI and loneliness has not been rigorously tested.…”
Section: Lonelinessmentioning
confidence: 99%
“…In addition, loneliness has been observed to be accompanied by marked physiological changes, including increased systemic inflammation, stress reactivity, abnormal neuroendocrinology, and higher blood pressure . Loneliness is also associated with cognitive impairment, depression, suicidal ideation, cardiovascular disease, pain, and functional impairments in activities of daily living (ADLs) . Loneliness is also related to increased health care utilization among older adults .…”
Section: Introductionmentioning
confidence: 99%